Feasibility and Effectiveness of Cognitive–Behavioral Therapy for Posttraumatic Stress Disorder in Preschool Children: Two Case Reports - Scheeringa, Michael S. (J Trauma Stress, 2007)
New evidence raises concerns that posttraumatic stress disorder (PTSD) in preschool children is unremitting over years even with unstructured community treatment. This report presents proof of concept of the feasibility and effectiveness of a structured therapy, cognitive–behavioral therapy (CBT), for preschool PTSD that follows a range of different traumatic events. Two cases are presented, including transcribed dialogue, from a motor vehicle accident and Hurricane Katrina, respectively. Three key CBT feasibility questions were examined; it was concluded that (a) young children can cooperate meaningfully in structured, trauma-related exposure exercises; (b) they can utilize relaxation techniques successfully; and (c) highly anxious parents do not inhibit their children’s improvement per se as long as they can facilitate the manual techniques. Clinicians need to be aware of emerging evidence-based treatment for preschool children.